Employee perception of logistics integration on supply chain performance in Malaysian telecommunication industry - Noraini, Ahmad (2022)
Given the telecommunication industry's increasing competitiveness and customer demand for lower cost and higher quality service, telecommunication companies must increase operational efficiency in order for their supply chain management to function optimally. In response to the demand for knowledge, the purpose of this study was to determine the relationship between supply chain management practice and supply chain performance, as well as whether or not this relationship is mediated by logistical integration. The present study was conducted among 361 respondents from 21 Malaysian telecommunication firms in Malaysia by applying a structural equation modeling with SmartPLS. Findings revealed that from the three factors of supply chain management, customer relationship and information-sharing associated with supply chain performance, the relationship between strategic supplier partnership and supply chain performance was not supported. Logistics integration mediated the relationship between information- sharing and supply chain performance but failed to mediate the effect of the logistics integration relationship in the relationship between strategic supplier partnership and supply chain performance. The study confirmed that applying the underpinning theory's Resource-Based View could be a promising framework for improving supply chain performance in the telecommunications industry. The study established that by sharing information with suppliers and creating customer relationships, supply chain performance may be improved through logistics integration. The study has implications for practitioners in the decision-making process of SCM procedures, particularly in the telecommunications industry.